Enhanced Efficiency of Tesla Turbines with Variable Disc Configurations in Indonesia: Peningkatan Efisiensi Turbin Tesla dengan Konfigurasi Cakram Variabel di Indonesia - Rosyid, Abdul; Fahruddin , A’rasy (Universitas Muhammadiyah Sidoarjo, 2024)
The rapid development of technology increases the demand for energy while non-renewable sources decline. This study explores the Tesla turbine, which converts fluid energy into mechanical energy using circular discs stacked with specific gaps. We tested three configurations with 4, 6, and 8 discs, each 0.3 mm thick, at Universitas Muhammadiyah Sidoarjo. Using direct observation, experimental testing, and literature review, we measured turbine performance with a digital tachometer and spring scale. Results showed that modifying the disc number effectively influenced energy output, offering insights for enhancing Tesla turbine efficiency as a renewable energy solution. Highlight: Tesla turbine converts fluid energy to mechanical using circular discs. Tested configurations: 4, 6, and 8 discs, each 0.3 mm thick. Study offers insights into enhancing Tesla turbine efficiency Keywoard: Tesla Turbine, Energy Conversion, Fluid Dynamics, Renewable Energy, Disc Configuration